Initial pole position estimation of the permanent magnet-excited linear synchronous motors using force control. - Nam, Đào Phương; Quang, Nguyễn Phùng (Journal of Computer Science and Cybernetics, 2012)
In recent times, linear motions are often indirectly realized by rotating motors, which cause some disadvantages. The use of motors which are able to create linear motions directly (linear motors) can prevent these disadvantages. The pole – position are the important parameter of permanent magnet linear synchronous motor and also one of the conditions to obtain the field orientated control structure. Some simulation and experiment results have solved the ability of this method.